2016
DOI: 10.1016/j.emcon.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of organophosphate flame retardants in dust from cars, homes, and offices: An international comparison

Abstract: a b s t r a c tConcentrations of a number of organophosphate flame retardants (PFRs) were measured in floor dust collected from living rooms in Australia (n ¼ 42), Canada (n ¼ 14), Germany (n ¼ 22), and Kazakhstan (n ¼ 9); cars from Australia (n ¼ 39) and Germany (n ¼ 19); and offices from Germany (n ¼ 25) and Kazahkstan (n ¼ 8). PFR concentrations in these samples were compared with each other and with previously reported data for PFRs in dust from similar microenvironments in the UK. Our data reveal signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…results showed a good agreement with both OPFR and PBDE concentrations previously reported in Australian indoor dust [36,37]. Compared with the concentrations found in other countries, OPFR concentrations here were lower than those in Germany [12], but comparable with those in Netherlands [38], Canada and Kazakhstan [36]. PBDE concentrations in this study were lower than those of the USA [39], but were similar to UK concentrations [40].…”
Section: Australian Indoor Dustsupporting
confidence: 89%
See 1 more Smart Citation
“…results showed a good agreement with both OPFR and PBDE concentrations previously reported in Australian indoor dust [36,37]. Compared with the concentrations found in other countries, OPFR concentrations here were lower than those in Germany [12], but comparable with those in Netherlands [38], Canada and Kazakhstan [36]. PBDE concentrations in this study were lower than those of the USA [39], but were similar to UK concentrations [40].…”
Section: Australian Indoor Dustsupporting
confidence: 89%
“…Fig 3 and Table S3 summarised the concentrations of OPFRs and PBDEs in Australian dust. results showed a good agreement with both OPFR and PBDE concentrations previously reported in Australian indoor dust [36,37]. Compared with the concentrations found in other countries, OPFR concentrations here were lower than those in Germany [12], but comparable with those in Netherlands [38], Canada and Kazakhstan [36].…”
Section: Australian Indoor Dustsupporting
confidence: 89%
“…The profiles of OPFRs in car dust showed a large variation among countries (Figure D). In general, car dust in this study was dominated by TBOEP, TCIPP, and TDCIPP; in Egypt, Kuwait, and the UK, it was dominated by TCIPP; in the Netherlands, Kingdom of Saudi Arabia, and Germany by TDCIPP; and in Pakistan and Australia by TPHP. Ali et al .…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, data on human exposure to OPFRs in various microenvironments are scarce for the German population. To the best of our knowledge, three studies have reported levels of OPFRs in dust from private homes, offices, and private cars, while only one study reported the occurrence of OPFRs in indoor dust from daycare centers in Germany.…”
Section: Introductionmentioning
confidence: 98%
“…For example, PFRs are commonly detected in dust samples collected in cars (e.g. Harrada, 2016). It is possible that exposure inside cars in the summer is higher due to higher temperatures.…”
Section: Resultsmentioning
confidence: 99%